PENGELOLAAN TAMBANG PASIR DAN DAMPAKNYA TERHADAP LINGKUNGAN HIDUP DI KABUPATEN BULUKUMBA DALAM PERSPEKTIF SIYASAH SYAR’IYYAH - Wiwin Hasrianti Rukmana; Syatar, Abdul (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2023)
This study aims to determine the management of sand mines on the environment in Bulukumba Regency from the perspective of Siyasah syar’iyyah. The type of research used is field research which is descriptive qualitative in nature by using normative juridical and syar’i normative approaches. The results of the study show that sand mining in Bulukumba Regency goes through the stages of preparation or excavation, desludging, refining, transportation and sale which in its management has an impact on soil mass, water becomes turbid, disturbance of aquatic biota, marginal land, pollutes and reduces water discharge, reduces land use management. land use, damaged roads and pollution. Siyasah syar’iyyah’s view of sand mining is that sand mining provides benefits to society and the government but also causes harm so that humans are required to avoid all behaviors that cause harm including environmental damage.